A new metabolic disorder in human cationic amino acid transporter‐2 that mimics arginase 1 deficiency in newborn screening. Issue 3 (21st February 2019) - Yahyaoui, Raquel; Blasco‐Alonso, Javier; Benito, Carmen; Rodríguez‐García, Enrique; Andrade, Fernando; Aldámiz‐Echevarría, Luis; Muñoz‐Hernández, María C.; Vega, Ana I.; Pérez‐Cerdá, Celia; García‐Martín, María L.; Pérez, Belén
Abstract: Purpose: We report a patient with a human cationic amino acid transporter 2 (CAT‐2) defect discovered due to a suspected arginase 1 deficiency observed in newborn screening (NBS). Methods: A NBS sample was analyzed using tandem mass spectrometry. Screen results were confirmed by plasma and urine amino acid quantification. Molecular diagnosis was done using clinical exome sequencing. Dimethylated arginines were determined by HPLC and nitrate/nitrite levels by a colorimetric assay. The metabolomic profile was analyzed using 1D nuclear magnetic resonance spectroscopy. Results: A Spanish boy of nonconsanguineous parents had high arginine levels in a NBS blood sample. Plasma and urinary cationic amino acids were high. Arginase enzyme activity in erythrocytes was normal and no pathogenic mutations were identified in the ARG1 gene. Massive parallel sequencing detected two loss‐of‐function mutations in the SLC7A2 gene. Currently, the child receives a protein‐controlled diet of 1.2 g/kg/day with protein‐and amino‐acid free infant formula, 30 g/day, and is asymptomatic. Conclusion: We identified a novel defect in human CAT‐2 due to biallelic pathogenic variants in the SLC7A2 gene. The characteristic biochemical profile includes high plasma and urine arginine, ornithine, and lysine levels. NBS centers should know of this disorder since it can be detected in arginase 1 deficiency screening.